Addressing Pediatric Obesity in Clinic - George G. A. Pujalte MD, FACSM; Isabella Ahanogbe MD; McKennan J. Thurston MD; Richard O. White MD, MSc; Alva Roche-Green MD, FAAP, FACP (SAGE Publishing, 2017)
There is an epidemic of pediatric obesity in the United States. In most cases, there is an excess in the amount of calories consumed, compared with the amount of calories expended. Numerous body systems are affected by pediatric obesity, with complications varying between boys and girls. Behavioral, genetic, and environmental factors affect the ability of children to avoid becoming obese. Primary care physicians should screen for obesity in children as much as possible. Associated risk factors for obesity should be uncovered. Methods of preventing obesity should be discussed routinely with children and their families. Healthy dietary habits are key, and so are family-oriented interventions, such as eating together at dinnertime. One hour of moderate to vigorous activity daily is recommended for children and adolescents. While pediatric bariatric surgery is an option, there are also numerous nonpharmacological and pharmacological measures available as management for pediatric obesity. Family-based approaches, such as reducing screen time, have been very successful. Non-weight-bearing exercises also help children and adolescents expend calories without causing injury to themselves. Family availability, activity preference, and developmental levels should all be considerations when managing pediatric obesity. Motivational interviewing may also be helpful, especially when customized for each specific patient and family. Clinicians will play an increasing role in terms of identifying, treating, and preventing pediatric obesity; measures that can be done in the clinic should be considered more and more.